Surgical procedure of extracting teeth for obtaining dental pulp for regenerative medicine in swine. (April 2015) - Sasaki, R; Matsumine, H; Watanabe, Y; Yamato, M; Ando, T
Dental pulp is a potential source of cells that can be used in cell replacement therapy for various nerve disorders, including stroke, spinal cord injury, and peripheral nerve defect. However, the validation of an animal model closely related to humans is needed in translational research. The miniature pig is a suitable experimental model in maxillofacial surgery, because its anatomical structure and size are similar to those of humans. However, the swine tooth is extremely long. The routine closed extraction procedure for harvesting dental pulp tissue causes root fracture. This report describes the details of a surgical procedure for tooth extraction. Four healthy 7–8-month-old male NIBS miniature pigs were used. Two mandibular deciduous right incisors (Di1 and Di2) were extracted in order to obtain dental pulp tissue. Gingival envelope incision with vertical-releasing incision was performed, and a full-thickness mucoperiosteal flap was made. The buccal alveolar bone was exposed and removed by osteotomy. Di1 and Di2 were extracted. Dental pulp tissue was obtained from these extracted teeth by splitting hard tissue. In this procedure, 9.8 ± 2.5 × 10 5 cells were obtained from the mandibular Di1 and Di2 ( n = 4).